The complete mitochondrial genome sequences of two Emberiza (Aves, Passeriformes) - Fangqing Liu; Janine Antalffy; Longying Wen (Mitochondrial DNA. Part B. Resources, 2019)
We sequenced the complete mitochondrial genome of Emberiza leucocephala (Pine Bunting; 16,754 bp in length) and E. elegans (Yellow-throated Bunting; 16,780 bp in length). Gene order and orientation are consistent with those of most avian mitochondrial genomes. The result of the phylogenetic analyses suggested that the classification of Melophus and Latoucheornis was monotypic genera, which suggest they should be placed within Emberiza.